2020
DOI: 10.1111/jam.14742
|View full text |Cite
|
Sign up to set email alerts
|

Vertical distribution of microbial communities and their response to metal(loid)s along the vadose zone–aquifer sediments

Abstract: Aims This study attempted to demonstrate the vertical shift in bacterial, archaeal and fungal communities along the vadose zone–aquifer sediments and their respective responses to environmental factors. Methods and Results We collected samples from the vadose zone and three aquifer sediments along a 42·5 m bore of a typical agricultural land. The results showed that the bacterial community shifted greatly with depth. The classes of Actinobacteria (19·5%) and NC10 (11·0%) were abundant in the vadose zone while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 99 publications
1
0
0
Order By: Relevance
“…This might be due to differences in environmental adaptations, cellular structure, and cellular metabolisms between bacteria and archaea (31)(32)(33). Our findings are consistent with those of other studies that have reported the dominant role of stochastic processes in structuring the soil archaeal communities in forests (18,43) and farmland (47). However, other studies have also revealed only a minor role of stochastic processes in governing the archaeal community assemblies in the Namib Desert (45) and in agricultural fields across eastern China (46).…”
Section: Discussionsupporting
confidence: 90%
“…This might be due to differences in environmental adaptations, cellular structure, and cellular metabolisms between bacteria and archaea (31)(32)(33). Our findings are consistent with those of other studies that have reported the dominant role of stochastic processes in structuring the soil archaeal communities in forests (18,43) and farmland (47). However, other studies have also revealed only a minor role of stochastic processes in governing the archaeal community assemblies in the Namib Desert (45) and in agricultural fields across eastern China (46).…”
Section: Discussionsupporting
confidence: 90%